QoS provisioning in a service-oriented architecture targeting the smart grid world. (2018) - Chrysoulas, Christos
In today's liberalised market of energy, dynamic selections of services (energy consumption or even energy production) and by extension of service providers are crucial. It is equally important for service providers to spot the one quality of service (QoS) module that offers the best QoS level in a given cost. Attributes like type of service, response time, throughput, availability and cost, form the basic set of attributes that should be taken into consideration when building a concrete/stable grid network. In the proposed QoS architecture, prosumers request services based on the aforementioned set of attributes. The prosumer requests the service through a QoS module. Afterwards, it is the QoS module's responsibility to seek the service provider that best serves the needs of the client.